Farmakolojik Vitreolizis - (:unkn) unknown (My University, 2015)
Farmakolojik vitreolizis, vitreus yapısının cerrahiye gerek kalmaksızın kimyasal olarak değiştirilerek etkili ve güvenli bir şekilde retinadan ayrılmasıdır. Bu amaçla günümüze kadar çeşitli ajanlar ve enzimler denenmiş, bunlar arasından klinik uygulamada en çok etkinlik gösteren iki enzim plazmin ve okriplazmin olmuştur. Amerikan Gıda ve İlaç Kurumu (FDA) tarafından semptomatik vitreo-maküla adezyonu tedavisi için 2012 yılında ruhsat alan okriplazminle farmakolojik vitreoliziste yeni bir dönem başlamıştır. Bu makalede enzimatik vitreolizis ve okriplazmin hakkında bilgi verilecek ve okriplazmin ile ilgili güncel çalışmalara değinilecektir

Pharmacologic vitreolysis is an alternative treatment to surgery, aiming to cause vitreous liquefaction and complete posterior vitreous separation from the retina effectively and safely. Several agents and enzymes have been explored for this purpose. Of these, plasmin and ocriplasmin have shown the most promise for clinical application. The recent approval by the US Food and Drug Administration of ocriplasmin for the treatment of symptomatic vitreomacular adhesion has brought new attention to the field of pharmacologic vitreolysis. This article summarizes enzymatic vitreolysis and current knowledge and status of investigations regarding ocriplasmin-induced pharmacologic vitreolysis, and offers some evidence-based considerations for its use
Pharmacologic Vitreolysis
Keywords: Göz Hastalıkları